Multi-part mirror for focusing diffuse light - Mitsuhiro MATSUMOTO (The Japan Society of Mechanical Engineers, 2017)
In the present study a multi-part mirror is developed for focusing only a scattered light effectively. The multipart mirror is composed from several elliptic mirrors. Several elliptic mirrors are installed on the surface of the multi-part mirror. Primary focal points of all elliptic mirrors lie on the surface of the multi-part mirror. Secondary focal points of all elliptic mirrors are located in the same point above the multi-part mirror. The mirror surface of elliptic mirrors is small; so many elliptic mirrors are densely placed on the multi-part mirror. A large amount of light passing from various directions through the primary focal points densely packed on the multi-part mirror surface is reflected from the mirror surface and focused in the secondary focal points. The multi-part mirror was designed as described above. Mirror surfaces of the elliptic mirrors comprising the multi-part mirror and location of primary focal points of the elliptic mirrors were designed. Design parameters necessary to densely place the elliptic mirrors on the multi-part mirror were determined. The actual multi-part mirror was manufactured using these determined design parameters. The manufactured multi-part mirror was exposed to a diffused light. The intensity of scattered light focused in the secondary focal points was measured. The measured light intensity shows the focusing efficiency of the multi-part mirror.